Predictive Value of Cough Frequency in Addition to Aspiration Risk for Increased Risk of Pneumonia in Dysphagic Stroke Survivors: A Clinical Pilot Study - Pekacka-Egli, Anna Maria (Brain Sci, 2021)
Background: Post-stroke dysphagia leads to increased risk of aspiration and subsequent higher risk of pneumonia. It is important to not only diagnose post-stroke dysphagia early but also to evaluate the protective mechanism that counteracts aspiration, i.e., primarily cough. The aim of this study was to investigate the predictive value of cough frequency in addition to aspiration risk for pneumonia outcome. Methods: This was a single-center prospective observational study. Patients with first-ever strokes underwent clinical swallowing evaluation, fibreoptic endoscopic evaluation of swallowing (FEES), and overnight cough recording using LEOSound(®) (Löwenstein Medical GmbH & Co. KG, Bad Ems, Germany ). Penetration–Aspiration Scale (PAS) ratings and cough frequency measurements were correlated with incidence of pneumonia at discharge. Results: 11 women (37%) and 19 men (63%), mean age 70.3 years (SD ± 10.6), with ischemic stroke and dysphagia were enrolled. Correlation analysis showed statistically significant relationships between pneumonia and PAS (r = 0.521; p < 0.05), hourly cough frequency (r = 0,441; p < 0.05), and categories of cough severity (r = 0.428 p < 0.05), respectively. Logistic regression showed significant predictive effects of PAS (b = 0.687; p = 0.014) and cough frequency (b = 0.239; p = 0.041) for pneumonia outcome. Conclusion: Cough frequency in addition to aspiration risk was an independent predictor of pneumonia in dysphagic stroke survivors.